ҚАРАҚАЛПАҚ БАЛАЛАР ФОЛЬКЛОРЫНДА АЙТПЫШЛАР - Абдалиева, П.; Амирлан, С.Е. (SCIENCE and SOCIETY, 2021)
It is said in this article about a kind of foster poetry of Karakalpak nation as facetious sayings. The reasons of facetious sayings are opened as a genre of originality and difference from other genres. On the basis of it we determine the importance of sayings in the formation of children’s speech, improving mother wit, extemporization, eloquence. Sayings are based on the question-answer foundation is considered to be Turkish nations ancient traditional genre.